Analisis Literatur tentang Dampak Media Interaktif Digital terhadap Peningkatan Tematik pada Siswa Sekolah Dasar - Nabila R., Riska; Mustika, Dea; Oktaviani, Anggi; Aswati, Putri; Husni, Nisa Amalia; Putri, Naila Syahrani (Universitas Al-Qolam Malang, 2025)
Thematic learning in elementary schools aims to integrate various competencies within a single, meaningful theme that is relevant to students' real-life experiences. However, in practice, this approach often faces challenges due to monotonous delivery methods that fail to engage learners. Interactive digital media serves as an alternative solution, offering more attractive and interactive content that aligns with 21st-century learning styles. This study aims to review scientific literature on the use of interactive digital media in thematic learning at the elementary level. The method used is a literature review of ten journal articles published between 2021 and 2025, sourced from Google Scholar. The results indicate that various forms of digital media—such as interactive PowerPoint, Canva-based animation videos, and multimedia using Flash—can enhance students’ understanding of thematic content and increase their motivation to learn. Nevertheless, challenges such as limited infrastructure, teacher readiness, and unequal access to technology remain obstacles in several schools. Therefore, strengthening teachers’ digital competencies and ensuring equitable technological support are essential for the effective implementation of interactive media in thematic education